Evolution of slamming load and flow field in water-entry process of trimaran ship section. (1st June 2020) - Zong, Zhi; Sun, Yifang; Jiang, Yichen; Sun, Tiezhi; Yu, Yiquan
Abstract: A slamming motion is a serious issue when a trimaran is sailing on waves. Therefore, it is necessary to study the pressure and vertical acceleration of the measuring point on the ship's surface, and the velocity of the fluid particle of the flow field at different dropping heights, using model tests. First, a vertical water entry model test of a trimaran model was conducted at three different heights. Then, the pressures of five measuring points (at the bottom of the main hull and near the cross deck) and the acceleration of the model were measured. In addition, pressure variations and acceleration peak values are analysed. The time-record curves of the pressure were then fitted using a Gaussian function. Finally, the flow field was obtained using the particle image velocimetry technique. The results show that the peak values of the points in the cross deck and the upside of the main hull were maximum at H = 20 mm; nevertheless, other pressure and peak values of the slamming acceleration measurement points increased as the dropping height increased. Further, the shapes of the pressure curves near the peak value were sharper for the model's bottom than at other positions. Moreover, the flow particle velocity at the bottom of the trimaran model and the free surface between the main and side hulls was higher. There was also a significant amount of pupple generated below the cross deck after the cross deck's slamming. Finally, as the drop height increased, the position of the air-water mixture trended towards the side hull. Highlights: The vertical entry water experiment for a trimaran section with the weight and moulded lines according to the real ship. The pressure curves were fitted by Gaussian Function in order to obtain the function expression of entry time. The velocity vector distribution of the flow field in each working condition has been measured by PIV during the slamming.